An assessment model for the training of medical postgraduate students in urology - Wentzel, Schalk Willem (University of the Free State, 2012)
The researcher realised that there was a need to revisit assessment of postgraduate students in Urology and therefore decided to conduct a study on the current assessment model in Urology. The aim of the study was to develop an assessment model for postgraduate students in Urology that would comply with the principles of Higher Education (HE) and also be acceptable and advantageous to both the postgraduate students and assessors in Urology. A study was undertaken to identify the changes that have taken place in assessment as well as the different principles of assessment that should be included in a sound assessment model. The study investigated the role of formative and summative assessment, feedback in assessment and quality assurance as part of assessment. The research included an investigation of the assessment methods that will be most suitable for the assessment of postgraduate students in Urology. The research undertaken in this study followed a quantitative approach with some elements of qualitative research. The researcher made use of a literature review, a questionnaire survey among Urologists in South Africa and a Delphi process that included experts in the fields of Urology and HE. In the questionnaire survey the participants were asked to answer questions about the changes in HE and the assessment methods available to assess postgraduate students in Urology. The questions in the questionnaire survey were compiled by the researcher with the help of the literature review. The information gathered by the questionnaire survey supported by the literature review enabled the researcher to prepare some statements that could be included in the proposed assessment model for registrars in Urology. The statements prepared by the researcher were presented to a Delphi panel and they were asked to rate the statements as essential, useful or unnecessary parts of the assessment model. The Delphi panel consisted of ten experts in Urology and HE that were selected by the researcher and his moderators. A four-round Delphi process took place from September 2011 until January 2012. A total of 189 statements were presented to the Delphi panel in Round One of the Delphi process. At the end of the fourth round of the Delphi process consensus was reached on 163 out of a possible 189 statements (86%). The researcher approached the compilation of the assessment model in three parts. In the first part the researcher proposed that assessors of postgraduate students in Urology should have adequate knowledge about assessment in HE. In the second part of the assessment model, the researcher proposed an assessment policy for the College of Urology and described the characteristics thereof. In the final part of the assessment model the researcher proposed the assessment methods that should form the framework of formative and summative assessment of postgraduate students in Urology. The researcher stressed the importance of the dissertation as the student’s contribution towards the available literature in their field of study and included some proposals on the format of the dissertation project. The results of the study indicated that there were areas in the current assessment model of postgraduate students in Urology that could be improved. The assessment model as proposed by the researcher could be considered by the College of Urologists for future use in the assessment of postgraduate Urology students. If accepted, the assessment model can also serve as an example for the other colleges of the Colleges of Medicine of South Africa to formulate an assessment model of their own. The project attempted to make a contribution towards the improvement of assessment in urology students. The assessment model, if implemented, may assist in improvement of quality assurance in and fairness, validity and trustworthiness of assessment. It will stimulate other researchers in the field of HE to pursue other aspects of assessment that warranted further research. The assessment model can be an effective and valuable instrument to enhance student learning and produce topclass Urologists to serve the needs of the South African public.

Die navorser het tot die besef gekom dat herevaluering van assessering in nagraadse studente in Urologie nodig was en het daarom besluit om navorsing te doen oor die huidige assesseringsmodel in Urologie. Die doel was om ‘n assesseringsmodel te ontwikkel vir nagraadse studente in Urologie wat in lyn sou wees met die beginsels van Hoër Onderwys (HO) en wat ook aanvaarbaar en voordelig sou wees vir die nagraadse studente en assessore in Urologie. ‘n Studie is onderneem om die veranderinge wat plaasgevind het in assessering en die beginsels wat ingesluit behoort te word in ‘n assesseringsmodel, te identifiseer. Die studie het die rol van formatiewe en summatiewe assessering, terugvoer tydens assessering en gehalteversekering in assessering ondersoek. Die navorsing het ook ‘n ondersoek na die geskikste assesseringsmetodes vir nagraadse studente in Urologie ingesluit. Die navorsing in hierdie studie het ‘n kwantitatiewe benadering gevolg maar het elemente van kwalitatiewe navorsing ingesluit. Die navorser het gebruik gemaak van ‘n literatuuroorsig, ‘n vraelys-opname onder Uroloë in Suid Afrika en ‘n Delphi-proses wat kenners op die gebied van Urologie en Hoër Onderwys ingesluit het. In die vraelys-opname is die deelnemers gevra om vrae te beantwoord oor die veranderinge in Hoër Onderwys en die assesseringsmetodes wat beskikbaar is om nagraadse studente in Urologie te assesseer. Die vrae in die vraelys-opname is saamgestel deur die navorser met behulp van die literatuuroorsig. Die inligting wat ingesamel is met die vraelys-opname ondersteun deur die inligting wat ingewin is met die literatuuroorsig het die navorser in staat gestel om sekere stellings te formuleer oor komponente van assessering wat ingesluit behoort te word by die assesseringsmodel vir nagraadse studente in Urologie. Die stellings wat deur die navorser voorberei is, is aan die Delphi-paneel aangebied en hulle moes besluit of die komponent wat deur die stelling uitgebeeld is essensieel, bruikbaar of onnodig is as deel van die assessringsmodel. Die Delphi-paneel het bestaan uit tien kenners op die gebied van Urologie en Hoër Onderwys en is deur die navorser en sy moderatore aangewys. ‘n Delphi proses wat vier rondtes ingesluit het, het plaasgevind vanaf September 2011 tot Januarie 2012. Altesaam 189 stellings is in Rondte Een aan die Delphi paneel aangebied. Aan die einde van Rondte Vier is konsensus bereik oor 163 van die 189 stellings (86%). Die navorser het die samestelling van die assesseringsmodel in drie dele aangepak. In die eerste gedeelte het die navorser voorgestel dat assessore betrokke by assessering van nagraadse studente in Urologie oor genoegsame kennis oor veranderinge in assessering in Hoër Onderwys moet beskik. In die tweede gedeelte van die assesseringsmodel het die navorser ‘n assesseringsbeleid vir die Kollege van Uroloë voorgestel en die eienskappe daarvan beskryf. In die laaste gedeelte van die assesseringsmodel het die navorser die assesseringsmetodes voorgestel wat die raamwerk moet vorm van die formatiewe en summatiewe assessering van nagraadse studente in Urologie. Die navorser het die belang van die proefskrif beklemtoon as die student se bydrae tot die beskikbare literatuur in sy/haar studieveld en ook voorstelle oor die formaat van die dissertasie ingesluit. Die uitslae van die studie het aangedui dat daar areas in die huidige assesseringsmodel vir nagraadse studente in Urologie was wat verbeter kon word. Die assesseringsmodel soos voorgestel deur die navorser kan oorweeg word deur die Kollege van Uroloë as die assesseringsmodel wat in die toekoms gebruik kan word tydens die assessering van nagraadse studente in Urologie. Indien dit aanvaar word, kan dit dien as voorbeeld van ‘n assesseringsmodel vir die ander lede van die Kollege van Geneeskunde van Suid Afrika om hulle eie assesseringsmodel te ontwikkel. Hierdie navorsingsprojek poog om ‘n bydrae te lewer tot die verbetering van assessering van nagraadse studente in Urologie. Indien hierdie assesseringsmodel implementeer word kan dit ‘n bydrae lewer om gehalteversekering van assessering te verbeter en te verseker dat assessering regverdig, geldig en betroubaar is. Dit sal ander navorsers in die veld van Hoër Onderwys stimuleer om navorsing te doen oor ander aspekte van assessering wat verdere navorsing regverdig. Die assesseringsmodel kan ‘n effektiewe en waardevolle instrument wees om studenteonderrig te verbeter en topgehalte Uroloë op te lei wat aan die behoeftes van die Suid Afrikaanse publiek voldoen.
Thesis (Ph.D. (Health Professions Education))--University of the Free State, 2012
Keywords: Appeal process; Assessment committee; Summative assessment; Assessment methods; Formative assessment; Assessment model; Feedback; Health Sciences Education; Knowledge about assessment; Outcomes-based education and training; Postgraduate students; Urology; Quality assurance; Assessment policy; Urology -- Study and teaching (Internship)